2011
DOI: 10.1158/1940-6207.capr-10-0295
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Survival in Postmenopausal Women with Breast Cancer: Results from the Women's Health Initiative

Abstract: Although studies have shown that physically active breast cancer survivors have lower all-cause mortality, the association between change in physical activity from before to after diagnosis and mortality is not clear. We examined associations among pre- and postdiagnosis physical activity, change in pre- to postdiagnosis physical activity, and all-cause and breast cancer–specific mortality in post-menopausal women. A longitudinal study of 4,643 women diagnosed with invasive breast cancer after entry into the W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
241
3
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(260 citation statements)
references
References 17 publications
(16 reference statements)
12
241
3
4
Order By: Relevance
“…13 Recent reports provided evidence that physical activity carried out 3 h per week decreases the BC-related morbidity and mortality. 43 In addition, lifestyle changes such as reduced alcohol consumption and to quit smoking are recommended. 13 In the past, numerous study results on the preventative effects of adequate supplementation of vitamin D (1000-2000 units per day) in postmenopausal women with osteopenia/osteoporosis have been reported.…”
Section: Practical Aspects Of the Treatment Of Ctiblmentioning
confidence: 99%
“…13 Recent reports provided evidence that physical activity carried out 3 h per week decreases the BC-related morbidity and mortality. 43 In addition, lifestyle changes such as reduced alcohol consumption and to quit smoking are recommended. 13 In the past, numerous study results on the preventative effects of adequate supplementation of vitamin D (1000-2000 units per day) in postmenopausal women with osteopenia/osteoporosis have been reported.…”
Section: Practical Aspects Of the Treatment Of Ctiblmentioning
confidence: 99%
“…Many authors report in their studies that high physical activity in individuals after breast cancer treatment can slow the disease progression and increase the cure rates. Irwin et al demonstrated that high physical activity (≥9 MET/week) in women treated due to breast cancer and its increase from low to high after treatment reduced the risk of cancer-related death by 39% (21,30). Studies of other teams confirmed these observations (18,(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 96%
“…Holmes et al demonstrated a reduction in the risk of death due to breast cancer in women who exercised (3-5 hours per week) after treatment compared to women with a sedentary lifestyle (18). Other research groups have confirmed these results (19)(20)(21)(22). Walsh et al and Daroux-Cole et al suggested that exercise stimulated the immune system in cancer patients (23,24).…”
mentioning
confidence: 77%
“…Both, obesity (Callee et al, 2003;Chlebowski et al, 2004; American Cancer Society, 2012; 2013) and physical activity (Chlebowski et al, 2004;Leitzmann et al, 2008;Irwin et al, 2011;American Cancer Society, 2012;2013) has been associated with increased breast cancer risk in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%